Galactic Globular Clusters: A new catalog of masses, structural parameters, velocity dispersion profiles, proper motions and space orbits. Issue Volume 14:Issue S351(2019) (May 2019) - Hilker, Michael; Baumgardt, Holger; Sollima, Antonio; Bellini, Andrea
Abstract: We collected radial velocities of more than 50.000 individual stars in 156 Galactic globular clusters (GGC) and matched them with HST photometry and Gaia DR2 proper motions. This allowed us to derive the GGC's mean proper motions and space velocities. By fitting a large set of N-body simulations to their velocity dispersion and surface density profiles, combined with new measurements of their internal radially dependent mass functions, we have determined their present-day masses and structural parameters, and for 144 GGCs their internal kinematics. We also derive the initial cluster masses by calculating the cluster orbits backwards in time applying suitable recipes to account for mass-loss and dynamical friction. The new fundamental parameters of GGCs are publicly available via an online database, which will regularly be updated.